Peningkatan Literasi AI Guru Sekolah Dasar Melalui Pelatihan Berbasis NotebookLM - Nur Choiro Siregar; Nurhayati Nurhayati; Yani Sugiyani; Ri Sabti Septarini; Dedy Alamsyah (Jurnal Pengabdian kepada Masyarakat UBJ, 2026)
The activity was designed as a community-engaged training program responding to teachers’ limited understanding of AI applications for instructional preparation, learning resource development, and ethical classroom use. Using a participatory descriptive approach, the program involved preparation, training implementation, direct practice, discussion, mentoring, and descriptive evaluation. The training materials covered basic concepts of AI, AI literacy for teachers, the introduction and operation of NotebookLM, the use of NotebookLM for developing teaching materials, and ethical considerations in AI-assisted education. Participants engaged in lectures, demonstrations, and hands-on activities, including uploading learning resources, generating summaries, developing learning questions, and preparing simple instructional materials. The results indicate that the training improved teachers’ conceptual understanding of AI and strengthened their practical ability to use NotebookLM as a digital learning assistant. Participants recognized the platform’s potential to reduce preparation time, organize learning resources, and support the creation of structured teaching materials. The activity also raised awareness that AI-generated outputs require verification, contextual adjustment, and alignment with learning objectives and student needs. These findings suggest that NotebookLM can serve as a practical tool for strengthening teachers’ digital competence and generative AI literacy. However, sustainable integration requires continuous mentoring, critical evaluation of AI outputs, and responsible pedagogical decision-making by teachers, especially in ensuring that AI also supports meaningful, inclusive, curriculum-aligned, and ethically grounded classroom practices in elementary education settings and future teacher-led innovation.